Inferences about fitness cost of antiretroviral drug resistance mutations: insights from the mutation dynamics during structured antiretroviral treatment interruption among individuals experiencing virological failure - Hunter, James Richard [UNIFESP] (2019)
This study reviews drug resistance mutation dynamics on both the pol and gag genes among individuals under antiretroviral virological failure who underwent structured treatment interruption (STI). The study involved a 12-week interruption in antiretroviral therapy (ART), monitoring of viral load, CD4+/CD8+ T cell counts, and sequencing of the pol gene to examine mutation dynamics from 38 individuals experiencing virological failure and harboring 3-class resistant HIV strains: nucleoside reverse transcriptase inhibitors (NRTI) non-nucleoside inhibitors (NNRTI) and Protease inhibitors (PI). Protease and reverse transcriptase regions of the pol gene were sequenced at baseline before STI and every 4 weeks thereafter from PBMCs and at baseline and after 12 weeks from plasma HIV RNA using population-based Sanger sequencing. Over the following 12 weeks, average viral load increased 0.568 log10 copies per milliliter. CD4+ T cell count decreased as soon as ART was withdrawn, an average loss of 99.0 cells/mL. Forty-three percent of the mutations associated with antiretroviral resistance in PBMCs disappeared and 57% of the mutations on the pol gene in plasma reverted to wild type although we had expected they would all do so. In PBMC, the PI mutations reverted more slowly than reverse transcriptase mutations. The patients are projected to need an average of 33.7 weeks against 20.9 (NRTI) or 19.8 (NNRTI) weeks. On the gag gene, patients had an average of 32.8 mutations per patient pre-STI declining to 27.2 at the end of the study (of a total of 507 codons studied) indicating that mutations did return to wild type although not as completely as previous research has indicated nor as had been shown on the pol gene. We also used our analysis of the gag gene mutation profile to drive a study of how the mutations to the gag substrates interacts with mutations directly to the protease region of the pol gene. These results suggest that gag regions outside the cleavage sites may have a larger role in drug resistance than has been previously asserted. The study is composed of two papers that are being published jointly, the first addressing the mutation dynamics on the pol gene and the second on mutations in the gag gene.